Aplikasi Pembelajaran Huruf Hijaiyah Berbasis Android (Studi Kasus: TK Islam Nur Arief) - Tommy Tullusstya; Dani (CV. Shofanah Media Berkah, 2023)
Hijaiyah letters are the initial foundation so that we can learn and also understand the teachings of the Islamic religion contained in the Qur'an. By learning hijaiyah letters we will be able to read the Qur'an more quickly and also be able to practice what is contained in it. Understanding and reading the Qur'an can be a life guide to be able to stay away from what is prohibited and practice what is good for life both in the world as in everyday life and also in society and in the hereafter in eternal life.In this modern era, learning is not difficult anymore. When we want to study, we just need to find a place to study, such as a school, kindergarten, and also a place for tutoring. However, sometimes even though we have studied somewhere, there are still some problems that interfere, especially in the learning process, and the common problem is about boredom during the learning process or the time that is felt to be lacking to learn and understand. In this Final Project, the author tries to answer these existing problems by raising them as a research title, namely the development of an application which will later be an improvement to an existing similar application and a variation of learning methods by parents. The application that will be made is an application for the development of learning hijaiyah letters and tajwid with the quiz method, and android-based simulation.By making this application, it is hoped that it will be able to provide improvements to existing similar applications and also be a variation of the learning methods used by parents in learning to their children when they are outside school hours or outside reciting hours at Al- Qur'an learning places.